Optimizing brinjal (Solanum melongena L.) health and yield through bio-organic amendments against Fusarium wilt - Jannatul Mauya; Khadija Akhter; Hasiba Kabir Mim; Marzia Rahman; Raihan Ferdous (PLoS ONE, 2025)
A field experiment was conducted to evaluate the effect of different bio-organic treatments, including control (T0), spent mushroom substrate-SMS (T1), vermicompost (T2), poultry manure (T3), biochar (T4), SMS with biochar (T5), SMS with poultry manure (T6), and SMS with vermicompost (T7) on the management of Fusarium wilt of brinjal (Solanum melongena L.). This experiment was followed by a Randomized Complete Block Design (RCBD) using three replications. Pathogen identification confirmed Fusarium sp. as the causal agent of wilt through morphological and pathogenicity tests. Growth attributes, yield, and disease incidence were recorded at various growth stages. The highest disease incidence was observed in the untreated control (T0), with values of 44.4%, 55.55%, and 77.77% at 25, 45, and 65 days after transplanting (DAT), respectively. In contrast, the lowest incidence was recorded in T5 (5.55%, 16.66%, and 16.66% at 25, 45, and 65 DAT), followed by T6, with both treatments showing statistically similar results. These findings were statistically significant compared to T0. The treatment of T5 significantly enhanced plant growth parameters, including plant height, number of leaves, and number of branches, alongside a substantial increase in yield (12.71 tons/ha), which was statistically similar to T6. These bio-organic amendments not only suppressed disease incidence effectively but also improved soil health, enhanced microbial diversity, and promoted vegetative growth and yield. The results indicate that the integration of SMS with Biochar or Poultry Manure is a sustainable and eco-friendly strategy for managing Fusarium wilt in brinjal cultivation, potentially replacing conventional chemical methods for enhanced productivity and soil health.